Pelatihan Pembuatan Media Pembelajaran di Kelas Rendah Bagi Guru SD-IK As-Sunnah Aceh Tengah - Nurjani (LSM Catimore dan Sahabat, 2023)
This training was motivated by the teachers as SDIK AS-Sunnah Aceh Tengah, most of them were overwhelmed by preparing effective learning media in low grades, because we all know students who are still in low grades quickly feel bored in learning, if the learning presented by teachers are less interesting to them. Therefore the authors are interested in providing a training that equips teachers in making effective learning media for elementary school students who are in low grades. In the training given by the author using the ABCD (Asset-Based Community Development) method, which has 4 steps namely: discovery, dream, design, and destiny. The results of this training can more or less provide provisions for teachers in knowing the characteristics of students, so that they can provide effective learning media for elementary school students who are still in the lower grades. Kerwords: Training; Low Class; Students Characteristics; Learning media.